Tunisian and Libyan Arabic Dialects: Common Trends - Recent Developments - Diachronic Aspects - Ritt-Benmimoun, Veronika (Estudios de Dialectología Árabe, 2017)
This tripartite volume with 18 contributions in English and French is dedicated to Tunisian and Libyan Arabic dialects which form part of the so-called Maghrebi or Western group of dialects. There are ten contributions that investigate aspects of Tunisian dialects, five contributions on Libyan dialects, and three comparative articles that go beyond the geographical and linguistic borders of Tunisia and Libya. The focus of "Tunisian and Libyan Arabic Dialects" is on linguistic aspects but a wider range of topics is also addressed, in particular questions regarding digital corpora and digital humanities. These foci and other subjects investigated, such as the syntactic studies and the presentation of recently gathered linguistic data, bear reference to the subtitle "Common Trends Recent Developments Diachronic Aspects".